2018
DOI: 10.2514/1.j056827
|View full text |Cite
|
Sign up to set email alerts
|

Multirotor Drone Noise at Static Thrust

Abstract: A first principles understanding of the sound field produced by multirotor drones in hover is presented. Propeller diameters ranging from 8 to 12 in. are examined and with configurations comprising an isolated rotor, quadcopter, and hexacopter configuration. The drone pitch, defined as the ratio of drone diameter to rotor diameter, is the same for all multirotor configurations and is valued at 2.25. A six-degree-of-freedom load cell is used to assess the aerodynamic performance of each configuration, whereas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(45 citation statements)
references
References 15 publications
2
42
1
Order By: Relevance
“…Two configurations are considered for the study. The configuration D1 is close to the well-documented drone Cyclone investigated by Misiorowski et al [18] and to the one reported by Tinney and Sirohi [17]. The configuration D2 is more representative of the DJI Phantom II studied by Intaratep et al [6], or of the Hubsan X4-Pro.…”
Section: Basic Aerodynamic Features Of Quadrotorssupporting
confidence: 82%
See 1 more Smart Citation
“…Two configurations are considered for the study. The configuration D1 is close to the well-documented drone Cyclone investigated by Misiorowski et al [18] and to the one reported by Tinney and Sirohi [17]. The configuration D2 is more representative of the DJI Phantom II studied by Intaratep et al [6], or of the Hubsan X4-Pro.…”
Section: Basic Aerodynamic Features Of Quadrotorssupporting
confidence: 82%
“…If noise enters the optimisation strategy as a criterion, unsteady loads must be considered as well. Consequently, the present work addresses realistic model distortions encountered in typical drone architectures, such as described in [6,17]. Two distortions are retained, namely the side-flow induced by advancing flight and the potential distortion around the supporting struts of a rotor.…”
Section: Introductionmentioning
confidence: 99%
“…Several concepts of DEP exist in the literature [11][12][13], but most of them are analysed for their applicability in designing BLI configurations [14,15]. Few studies have been conducted so far on the aeroacoustic properties of interacting propellers and are mainly related to counter-rotating propellers [16,17] and drones [18][19][20][21][22], where the distance between rotor hubs is a crucial aspect. In Reference [23], numerical aeroacoustic analyses of innovative propeller geometries have been carried out, accounting for a single propeller mounted on a wing.…”
Section: Introductionmentioning
confidence: 99%
“…The PSD estimate was also examined using premultiplied spectra [19], with the goal of filtering noise to clearly show contributions of the blade pass frequency (BPF) harmonics. The PSD for premultiplied spectra was calculated with segments of length = 2 /Ω where Ω is the rotational speed.…”
Section: Data Reductionmentioning
confidence: 99%
“…where ( ) is the Heaviside step function and: There are numerous other wavelets available for analysis, each with relative merits [19,20,22,24], but the Morse wavelet is well-supported by the cwt() function [25] and can be configured for different use cases. The generalized Morse wavelet is parameterized with the time-bandwidth product, 2 = :…”
Section: Data Reductionmentioning
confidence: 99%